Socio-ecological predictors of participation and dropout in organised sports during childhood - Vella, Stewart A (My University, 2014)
Objective: To investigate the longitudinal association between sports participation and parent-reported health-related quality of life in children. Study Design: Cohort study using data drawn from the Longitudinal Study of Australian Children in waves 3 (2008) and 4 (2010). Participants were a nationally representative sample of 4,042 Australian children aged 8.25 (SD = 0.44) years at baseline, and followed up 24 months later. Results: After adjusting for multiple covariates, children who maintained participation in sport between the ages of 8 and 10 years had higher parent-reported health-related quality of life at age 10 (Eta2 = .02) compared with: children who did not participate in sport (p = <.001); children who commenced participation after 8 years of age (p = .004); and, children who dropped out of sports prior to 10 years of age (p = .04). Children who participated in both team and individual sports (p = .02) or team sports alone (p = .04) had greater health-related quality of life compared to children who participated in individual sports alone (Eta2 = .01). The benefits of sports participation were strongest for girls (p < .05; Eta2 = .003). Conclusions: Children’s participation in developmentally-appropriate team sports helps to protect health-related quality of life and should be encouraged at an early age and maintained for as long as possible. This is particularly important for girls. The benefits are significant at a population level.
International Journal of Behavioral Nutrition and Physical Activity
Keywords: Activities -- Children's activities; Activities -- Leisure and lifestyle; Child Development -- Physical; Childhood and child development; Child Development; Activities; Leisure and lifestyle; Physical; Children's activities; Childhood and child development